Fisher-Yates and fuzzy Sugeno in game for children with special needs - Diena Rauda Ramdania; Mohamad Irfan; Salma Nuralisa Habsah; Cepy Slamet; Wisnu Uriawan; Khaerul Manaf (Universitas Ahmad Dahlan, 2020)
As a country that has its language, English is an international language that needs to be mastered. Until now, the mastery of English in Indonesian on an international scale is in a low category. Learning English should be taught to children from an early age. For children with special needs, special learning methods are needed so that the material is conveyed. Educational games can be used as an interesting learning media. In this study, an English educational game was created that had the concepts of a quiz, rearrange, and matching. Fisher-Yates algorithm was applied to randomize the questions so that the questions that came out varied. Fuzzy Sugeno algorithm is also applied to the scoring calculation, with input variables of time, value, and the number of stars obtained. The system test outcomes show that the application of the Fisher-Yates algorithm was successful because every question that came out was randomized. The application of the Fuzzy Sugeno algorithm happened also successful because of the high degree of accuracy. Besides, the use of games shows there is an increase in student understanding as evidenced by the acquisition of grades. The results of the average value in doing the test is from 80.41 to 88.3 after playing the game.